Analisis Implementasi Kegiatan Pemberantasan Buta Aksara Al-Qur’an di Kecamatan Lumbang Kabupaten Pasuruan Jawa Timur - Sofiyulloh; Mutmainnah, Lailatul (Universitas Nahdlatul Ulama Pasuruan, 2023)
The Qur'an is the highest authority in the Qur'an as a fundamental source for faith, worship, ethics and law. This study aims to determine the efforts to eradicate Al-Qur'an illiteracy in Lumbang sub-district, Pasuruan district. This study uses qualitative research methods using three approaches, namely: pedagogical approach, psychological approach and sociological approach. The data in this study were obtained through primary data and secondary data, namely observation and interviews. The research instruments were in the form of observation guidelines, interview guidelines and documentation. The results of this study indicate that the form of government and community cooperation in efforts to eradicate Al-Qur'an illiteracy in Lumbang District, Pasuruan Regency is really well realized. The forms of government and community cooperation are: government and community cooperation in the form of labor contributions, government and community cooperation in providing ideas, government and community cooperation in material donations and government and community cooperation in providing moral support. Cooperation between the government and the community in efforts to eradicate al-Quran illiteracy in Lumbang District, Pasuruan Regency, namely an approach with learning citizens, fun learning, activities outside of learning and motivating residents to learn the Koran. There are three opportunities in alleviating Al-Qur'an illiteracy, namely the existence of schools, facilities and infrastructure and management. Government and community cooperation in efforts to eradicate Al-Qur'an illiteracy has many benefits including: Establishment of TK/TPA, construction of mosques and establishment of majlis ta'lim. With this collaboration, the people of Lumbang Sub-district have become more pious and have faith in God Almighty, have noble character, are independent, have personality, and are physically and spiritually healthy.